PENGARUH PENGGUNAAN DOSIS PUPUK NPK MUTIARA (16 – 16 – 16) dan PUPUK KOMPOS TERHADAP PERTUMBUHAN dan HASIL TANAMAN SAWI (Brassica Juncea L) - Rizon Stefan Tarigan; Swati Sembiring; Donatus Dahang (Universitas Quality, 2021)
This study aims to determine the effect of the use of Mutira NPK fertilizer dosage (16-16-16) and Mabar compost fertilizer on the growth and yield of mustard plants (Brassica juncea L). This research will be conducted in Cingkes, Dolok Silau District, Simalungun Regency, North Sumatra, with an altitude of + 1,150 m above sea level. This research will be conducted in October 2019 - November 2019. This research uses factorial randomized block design (RBD) consisting of 2 treatment factors and 3 replications, namely: factor I with symbol (M) with a dose of M0: 0 gr / plot (control), M1: 18 gr, M2: 36 gr, M3 : 54 gr, and factor II with the symbol (K) with a dose of K0: 0 gr / plot (control), K1: 200 gr, K2: 400 gr, K3: 600 gr. So that obtained 16 treatment and repeated 3 times. Data from the observations were then performed analysis of variance with a F test of 5% level. If there is a significant difference (p <0.05), the test is continued with the DMRT test. The results showed that the treatment of the combination of NPK Mutiara fertilizer (16-16-16) and Mabar compost had a significant effect (p <0.05) on the variable growth of plant height, number of leaves, leaf area, plant wet weight, plant dry weight, diameter hump.